Model Prediction of Built-Up Land Use on Flood-Prone Areas (a Systematic Literature Review) - Mardalena, Ayu (BUMI: International Journal of Environmental Reviews, 2024)
Land use is dynamic due to the influence of population growth in an area. High population growth leads to uncontrolled and unplanned changes in land use in an area, resulting in environmental damage, especially in disaster-prone areas. The aim of this study is to review various models suitable for predicting changes in land use concerning flood-prone areas using a literature review method with PRISM guidelines and visualizing literature results using VosViewer software (1.6.19). The results of this study show that SD (System Dynamic Model) and CA-MC (Cellular Automata – Markov Chain) are the most commonly used models in land use change prediction. Meanwhile, the variables most suitable for land use studies, especially built-up land in relation to flood disasters, are population, growth rate, rainfall, slope, GDP, distance from (roads, rivers, and city centers), and LULC.